2021
DOI: 10.32598/bcn.2021.1204.2
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of Long-term Exposure to Extremely Low-frequency Electromagnetic Fields With Different Values on Learning, Memory, Anxiety, and β-amyloid Deposition in Adult Rats

Abstract: Background: Extremely low-frequency electromagnetic fields (ELF-EMFs) have gathered significant consideration for their possible pathogenicity. However, their effects on nervous system functions were not fully clarified. In this study, our aim was to assay the effect of ELF-EMFs with different intensity on memory, anxiety, antioxidant activity, beta amyloid (Aβ) deposition and microglia population in rats. Materials and Methods: Fifty male adult rats were randomly separated into 5 groups; four groups exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Serotonin in the hippocampus is involved in anxiety-like behavior [ 51 ] and the serotonergic system in hippocampus regulates anxiety-like behavior [ 52 ]. Considering that prenatal stress is one of the most common factors in inducing anxiety-like behavior in offspring in modern societies [ 53 55 ] and on the other hand due to the confinement of modern living environment with ELF-EMF and the anxiogenic effect of ELF-EMF [ 25 , 26 , 56 , 57 ] and also considering the key role of the hippocampus in anxiety-like behavior [ 31 ], we hypothesized that if these two factors may have synergic effect of inducing anxiety-like behavior via metabolic changes in hippocampus or the interaction of these two factors can reduce their ability to create anxiety-like behavior. For the first time, to our knowledge, our study simultaneously investigated anxiety-like behavior, neurostroids formation and metabolism, cryptochrome2 expression as a marker of circadian rhythm, glutamate receptor activation, and serotonin production in the hippocampus of female rat offspring which were prenatally stressed and/or exposed to EMF.…”
Section: Introductionmentioning
confidence: 99%
“…Serotonin in the hippocampus is involved in anxiety-like behavior [ 51 ] and the serotonergic system in hippocampus regulates anxiety-like behavior [ 52 ]. Considering that prenatal stress is one of the most common factors in inducing anxiety-like behavior in offspring in modern societies [ 53 55 ] and on the other hand due to the confinement of modern living environment with ELF-EMF and the anxiogenic effect of ELF-EMF [ 25 , 26 , 56 , 57 ] and also considering the key role of the hippocampus in anxiety-like behavior [ 31 ], we hypothesized that if these two factors may have synergic effect of inducing anxiety-like behavior via metabolic changes in hippocampus or the interaction of these two factors can reduce their ability to create anxiety-like behavior. For the first time, to our knowledge, our study simultaneously investigated anxiety-like behavior, neurostroids formation and metabolism, cryptochrome2 expression as a marker of circadian rhythm, glutamate receptor activation, and serotonin production in the hippocampus of female rat offspring which were prenatally stressed and/or exposed to EMF.…”
Section: Introductionmentioning
confidence: 99%
“…Different parameters may lead to opposite conclusions. It has been demonstrated that long-term exposure to very low frequency electromagnetic fields has pro-anxiety and oxidative stress-inducing effects in rats (20) and found a similar phenomenon. In contrast, Qubty et al (21) found no difference in anxiety-like behavior in EPM experiment of mice exposed to radiofrequency EMR.…”
Section: Discussionmentioning
confidence: 81%
“…Different parameters may lead to opposite conclusions. It has been demonstrated that long-term exposure to very low frequency electromagnetic fields has pro-anxiety and oxidative stress-inducing effects in rats ( 20 ). Zhang et al ( 2 ) studied the behavioral effects of 1.8 GHz radiofrequency fields on mice and found a similar phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Faraji et al, 2021 [62] Fifty male adult rats were exposed to extremely low-frequency electromagnetic fields (ELF-EMFs) to study the impact on memory, anxiety, antioxidant activity, beta-amyloid deposition, and microglia population.…”
Section: Reference Study Outcomementioning
confidence: 99%